Decarbonization Efforts in Africa: Successes, Opportunities, and Challenges for Promoting the use of Renewable Energy by Social Economy - Ibbih, Joseph Mamman; Nyako, Nicodemus Samson (Social Entrepreneurship Review, 2024)
Background: While Africa contributes minimally to global warming, it remains disproportionately vulnerable to the adverse impacts of climate change, including reduced agricultural productivity and erratic rainfall patterns. In response, African governments and policymakers have devised strategies aimed at mitigating climate change effects and promoting renewable energy adoption, decarbonization, and sustainable development pathways. Research objectives: This article aims to explore the intersection of decarbonization and the social economy sector in Africa, particularly in promoting renewable energy utilization. It seeks to examine the challenges and opportunities associated with integrating decarbonization efforts within social economy frameworks on the continent. Research design and methods: The study employs a narrative methodology coupled with content analysis to investigate the dynamics of decarbonization within the context of the social economy in Africa. It assesses the existing initiatives, policies, and challenges related to promoting renewable energy adoption and decarbonization strategies. Results: The findings indicate that while there is a growing recognition of the importance of decarbonization and renewable energy in Africa’s social economy sector, challenges such as limited access to technology, funding, and infrastructure persist. Conclusions: Addressing these obstacles is crucial for advancing decarbonization and climate change mitigation efforts across the continent.